The Impact of the ASEAN Curriculum Framework on Regional Educational Integration: Opportunities, Challenges, and Implications - Balqis, Siti (PT. Batari Edu Calya, 2025)
The integration of Southeast Asia through ASEAN extends beyond politics and economics into education. A central instrument in this process is the ASEAN Curriculum Framework (ACF), introduced in 2012 to harmonize curricula across member states. This article examines the impact of the ACF on regional educational integration, focusing on policy dimensions, curriculum practices, and academic mobility. A descriptive qualitative approach was employed through a literature review of ASEAN official documents, UNESCO reports, and academic publications from 2012 to 2024. Findings indicate that the ACF contributes to curriculum harmonization, enhances 21st-century competencies, and strengthens ASEAN identity. Furthermore, the framework supports academic mobility via the ASEAN University Network (AUN) and the ASEAN Credit Transfer System (ACTS). Nevertheless, significant challenges persist, including disparities in educational quality, financial constraints, and inconsistencies in evaluation systems. The study concludes that the ACF holds considerable potential for advancing regional educational integration, but its success depends on strong political commitment, financial support, and readiness of national education infrastructures.